The effects on production of milking crossbred suckler cows grazing a semi-arid area of Kenya - Anindo, D.O.; Topps, J.H. (1993)
Three experiments were conducted in successive years using 32, 53 and 74 crossbred suckler cows respectively, in a semi-arid area close to Nairobi, Kenya. The cows were mated seasonally to calve approximately 1 month before the rainy season (March to May). A 2 X 2 factorial experimental design with milking and supplementation (2 kg concentrate/head per day) as the main treatments was used. The effects of milking (or not milking) supplementing (or not supplementing) cows were examined by measuring liveweight, condition score and milk yields. The cows used in this 3-year study (experiments 1, 2 and 3) were Ayrshire, Friesian or Simmental breeds crossbred with foundation females of Boran, East African Shorthorn, Zebu, Sahiwal and their crosses with Hereford. Weight loss during early lactation differed between the experiments. The dams in Experiment 2 lost significantly more liveweight because of the adverse effects of lower rainfall on grass growth in that year. Milking significantly exacerbated weight loss in the cows in the first 12 weeks of Experiment 2 (P<less or =>0.01). While supplementation either significantly increased liveweight gains or significantly reduced liveweight losses (P<less or =>0.01), it did not affect the total milk yield (P>0.05). The mean (<+->s.e.) yield was 418<+->36.1 kg. There was a decrease in body condition score (1-9) scale, 1 being very lean and 9 very fat, by an average of 3 units by the end of Experiment 2, in the 2 groups of cows that were not supplemented, but this was not significant (P>0.05). Similarly, very little change with time was recorded in Experiment 3. The results indicate that under the environmental conditions that prevail in the area, crossbred cows may be milked during the first 6 months of lactation to give an average total yield of approximately 400 kg without markedly reducing the weight of the cows. However, where grass growth is poor because of lower rainfall, weight losses are likely to be exacerbated.